Accounting for apparatus function when registering experimental data: peculiarity of choosing regularization parameter by L-curve criterion at deconvolution of the spectrum - A. M. Sokolov (Ядерна фізика та енергетика)
Within the framework of the problem of spectrum deconvolution, variant of the choice of the regularization parameter by criterion of the L-curve, based on the displacement along the points of the L-curve graph, is proposed. An analysis of dependencies on which the L-curve based is done. The L-curve itself is interpreted as a graph of the complex function of the norm of a regularized solution from the residual, and its similarity to the graph of the residual is noted.